Adverse Events With the Use of rhBMP-2 in Thoracolumbar and Lumbar Spine Fusions. Issue 5 (June 2015) - Lubelski, Daniel; Abdullah, Kalil G.; Steinmetz, Michael P.; Alvin, Matthew D.; Nowacki, Amy S.; Chakka, Srita; Benzel, Edward C.; Mroz, Thomas E.
<x xml:space="preserve">Abstract</x> Study Design: Retrospective chart review. Objective: To describe the adverse outcomes associated with the use of rhBMP-2 in thoracolumbar and lumbar fusions. Summary of Background Data: rhBMP-2 has been increasingly used in spinal fusions over the past decade. Early studies reported that the use of rhBMP-2 is associated with decreased operative time, blood loss, and pain scores, as well as improved fusion rates. Recent investigations have shown rhBMP-2 to be associated with various complications occurring at incidences ranging from 0% to 100%. Methods: Using the institutional electronic medical records, we retrospectively reviewed all patients between January 2002 and September 2010 that underwent thoracolumbar and lumbar spine fusion with BMP. Patient demographics, operative, and outcome/complication information was collected. Results: A total of 547 patient charts were reviewed with a mean follow-up time of 17 months. Mean age was 58 years. Forty-one percent of patients had undergone previous spine surgery. Thirty-nine percent of patients had a PLIF/TLIF, 29% underwent a PLF, and 20% an ALIF. No relevant differences in the patient characteristics and complications were identified between the various surgical approaches. For all approaches, having undergone a previous spine surgery was associated with increased incidence of radiculitis, reoperation, and pseudoarthrosis (P=0.005, 0.0008, 0.05, respectively) as compared with those without previous spine surgery. Being a current smoker at the time of operation was associated with increased rate of radiculitis (P=0.03) as compared with nonsmokers. Conclusions: The use of rhBMP-2, in this study, had an incidence of radiculitis, pseudoarthrosis, and reoperation that was similar to the rates in historical controls without rhBMP-2. Complications do not differ by surgical approach, but are more likely in current smokers and those undergoing revision surgery. A prospective study is warranted to further delineate the adverse event profile of rhBMP-2 and the variables that are likely to affect it (ie, type of surgery, carrier, and dose).